(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This Study at Bestlink College of the Philippines examined the coping strategies of senior high school HUMSS class mayors. According to the study’s findings, the majority of class mayors are female, and that occurs between the ages of 17 and 19. Additionally, it is stated that by accomplishing their given tasks, they have improved their academic performance and time management. Class mayors, however, have faced challenging circumstances as student leaders. The study’s recommendation was to believe in your ability to complete the task at hand rather than putting unnecessary pressure on yourself to complete it. Your body responds to what you think.